Energy Statistics Yearbook 2019 - United Nations (United Nations, 2022)
The 2019 Energy Statistics Yearbook is the sixty-third issue in a series of annual compilations of internationally comparable statistics summarizing world energy trends. Annual data for 225 countries and areas for the period 2016 to 2019 are presented on production, trade, and consumption of energy: solids, liquids, gaseous fuels, electricity, and heat, covering both renewable and non-renewable sources of energy. In addition, per capita consumption series are also provided for all energy products. Graphs are included to illustrate historic trends and/or changes in composition of production and/or consumption of major energy products. Special tables of interest include: international trade tables for coal, crude petroleum, and natural gas by partner countries – providing information on direction of trade; selected series of statistics on renewables and wastes; refinery distillation capacity; and a table on selected energy resources.